Induction of flowering and increasing fruit yield and quality in pomegranate (Punica granatum L.) cv. 'Bhagwa' by application of certain chemicals (Current Horticulture, 2024)
The field trail was conducted at ICAR- IIHR, Bengaluru to assess the effect of different chemicals (Nitrobenzene @ 1.0 ml, 1.5 ml and 2.0 ml/litre, Cycocel @ 500 ppm, 1000 ppm and 1500 ppm, Uracil @ 25 ppm and 50 ppm, Cycocel @ 1000 ppm + Uracil @ 25 ppm and Cycocel @ 1500 ppm + Uracil @ 50 ppm) on flower induction, fruiting and yield parameters in tissue cultured plant propagules of pomegranate (Punica granatum L.) cv. 'Bhagwa' during 2016-17 at ICAR-IIHR, Bengaluru. The foliar application of Cycocel @ 1500 ppm gave a significantly increased number of hermaphrodite flowers (287.84) and intermediate flowers (254.14) per plant, thereby increasing the percentage of fruit setting (86.10 %) and number of fruits (156.66) per plant. Thus fruit yield (54.53 kg/plant and 21.81 tonnes/ha), fruit weight (348.32 g), fruit length (8.53 cm) and fruit volume (333.93 ml) increased significantly. Consequently, foliar application of Cycocel @ 1500 ppm led to a significant reduction in number of male flowers (219.70) produced per plant. However, fruit width was non-significant among treatments.
Keywords: Flowering; Fruit yield; Cycocel; Fruiting; Uracil; Fruit width